ATTENTION DEFICIT HYPERACTIVITY DISORDER IN CHILDREN: THEORETICAL ASPECTS - Svetlana JELEASCOVA (Acta et Commentationes, Sciences of Education, 2022)
The article examines the theoretical aspects of Attention Deficit Hyperactivity Disorder in children. The problems of the evolution of views on the disease are touched upon, and a review of current trends in the development of the issue is made.